HUBUNGAN ANTARA KECEMASAN DENGAN PENYESUAIAN DIRI PADA MAHASISWA BIDIKMISI TAHUN PERTAMA DI UNIVERSITAS DIPONEOGORO - KOSMAS SESKOADI; Annastasia Ediati (Faculty of Psychology, Diponegoro University, 2017)
First year student need to adjust with different social and academic circumstances than high school. In the process they may find difficulties that lead to anxiety. The purpose of this research is to find the relationship between anxiety and adjustment on Bidikmisi’s first year student in Diponegoro University. Population of this study is 1.157 students. Try out test were given to 56 students. Data were collected from 174 students with convenience sampling technique. Data analyzed by Spearman Rank Correlation. Data measured by Adjustment Scale (26 item; α = 0,873) and Anxiety Scale (28 item; α = 0,905). The scale that was used to measure anxiety is SCARED (Screen for Child Anxiety Related Emotional Disorder). Spearman’s Correlation Test show that there is a significant negative correlation between anxiety and adjustment (rs = - 0,357; p < 0,01). The result is tje lower anxiety then the higher adjustment, vice versa. The potential strength of SCARED is it may an effective screening tool for all disorders of anxiety. Further researchers may use another measure instrument that suit their research purpose. Bidikmisi student may keep learning to adjust in college life. University may take part in developing adjustment skill for students by arrange training program and provide counseling service for keep mental health in a good state.